LEADERSHIP IN LOCAL SELF-GOVERNMENT AS A TOOL FOR ANALYTICAL ACTIVITY AND COMMUNICATIVE ENSURANCE OF INCLUSIVE TERRITORIAL DEVELOPMENT - SHESTAKOVSKA, Tetyana; GOLOLOBOV, Serhiy; KYRYCHENKO, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In modern conditions, local self-government plays a key role in ensuring sustainable socio-economic development of territories. The ability of local community leaders to form effective policies based on analytical data and open communication is a determining factor in successful governance. This issue becomes especially relevant in the context of martial law and post-war reconstruction, when communities face multidimensional challenges - from humanitarian crises to the need to quickly make decisions on economic development. Leadership in local self-government bodies today is not only a tool for effective management, but also an important means of communication support. The interaction of local authorities with the public, business and international partners allows to increase the level of trust and involvement of the population in decision-making processes. An important aspect is the development of analytical activities based on digital technologies, real-time data and modern forecasting methods. This contributes to increasing the efficiency of management processes and reducing the level of uncertainty in decision-making. Special attention should be paid to the communication policy of local government leaders. During times of crisis and transformation, there is a growing need for transparent mechanisms for informing citizens, ensuring two-way communication between the authorities and the public, and using digital communication tools. The use of integrated approaches to crisis management allows for the creation of more effective mechanisms for interaction between authorities, public organizations, and the private sector. Inclusive territorial development is another important aspect of effective local governance. It provides for equal access to resources and participation in planning the future of the community by all social groups, including people with disabilities, youth, and representatives of vulnerable categories of the population. The main challenges faced by local leaders in modern conditions are highlighted, and ways to overcome them are proposed by introducing innovative approaches to management, strengthening analytical mechanisms, and expanding opportunities for public participation in decision-making.
Keywords: territorial development; inclusive development; public administration; decentralization; local self-government; leadership; communication support; analytical activities